TH2.5 Evaluation of Radiological and Multimodal Prognostic Models in Discriminating Patients by Overall Survival in a Large Single Centre Cohort of Peri-Hilar Cholangiocarcinoma Patients. (9th August 2022) - Bird, Nicholas; Manu, Nichola; Shehata, Zak; Fenwick, Stephen; Jones, Robert; Malik, Hassan
Abstract: Aims: Several putative prognostic models have been developed to stratify patients with peri-hilar cholangiocarcinoma (PHC) by Overall Survival (OS). The objective of this study was to evaluate the utility of these models in determining prognosis for all patients presenting to a tertiary referral centre with PHC. Methods: Three hundred and two patients diagnosed with PHC referred to a regional tertiary referral centre between 2008 and 2019 had their demographic and survival data retrospectively analysed from a prospectively held database linked to Hospital Episode Statistics and Somerset Cancer Registry data. Univariate and multivariate modelling was utilised to determine significant prognostic variables. Concordance indices were constructed for the prognostic models to determine internal validity within the cohort. Results: Multivariate analysis demonstrated that: pre-interventional ECOG status (p 0.02); bilirubin levels (p 0.001); resectional status (p 0.001) and Mayo Clinic (MC) model (p 0.003) were significant predictors of OS. MC staging system demonstrated utility in stratifying patients by OS in pre-interventional patients with peri-hilar cholangiocarcinoma in all comers (p 0.001) and patients who did not progress to resection (p=0.021). There was strongly significant concordance between pre-intervention MC staging and OS in all comers in this cohort (C-index 0.59). Conclusions: This study has validated the use of the MC model in a pre-interventional clinic setting. Bilirubin, a standardised easily obtainable serological biomarker, should be considered for incorporation into the MC model to refine patient stratification by OS.